Evaluation Intravenous Drip Cephazolin Prophylaxis of Breast Cancer Surgery Site Infection. Issue 6 (September 2017) - Yang, Sufang; Liu, Guohua; Tang, Danling; Cai, De
Abstract : Purpose: The efficacy of antibiotic prophylaxis for the prevention of surgical site infection (SSI) after breast cancer surgery remains uncertain. The authors of a recent Cochrane meta-analysis based on 15 randomized trials were unable to draw a definitive conclusion. The purpose of this study was to determine the effectiveness of prophylactic antibiotics for the prevention of SSI after breast cancer surgery and the risk factors for SSI. Methods: Breast cancer patients who underwent mastectomy at the authors' institution were enrolled in this study. All the patients give cephazolin by intravenous drip within 1 hour before surgery. Surgical site infection was defined using Centers for Disease Control criteria. Risk factors were abstracted from the electronic medical record. Pearson χ 2 test, Student t test, and multivariable logistic regression were used for the analysis. Results: Four hundred fifty-eight patients undergoing mastectomy were enrolled in this study, including 293 with intravenous drip cephazolin and 165 without. Among them, an overall SSI rate of 6.1% was observed; 4.2% of patients without prophylactic antibiotics developed SSI compared with 7.2% with antibiotics ( P = 0.210). Factors associated with SSI were hypertension, diabetes, length of stay (d), age, and length of stay. Weight, duration of surgery, No. of drains, surgical procedure, and type of breast disease were not associated with increased SSI rates. Conclusions: Surgical site infection rates among patients who did and did not receive cephazolin after mastectomy had no significantly different. What is more, the authors should focus on advanced age, hypertension, diabetes, length of stay, and length of stay to decrease development of postoperative SSI rates.